A revision of the subgenus Xizicus (Paraxizicus) Liu, 2004 (Orthoptera: Tettigoniidae: Meconematinae) - Feng, Jiyuan; Chang, Yanlin; Shi, Fuming (Zootaxa, 2016)
The paper reviews the subgenus Xizicus (Paraxizicus) Liu, 2004, and describes one new species, i.e. Xizicus (Paraxizicus) furcistylus sp. nov. A key to the species and the distribution data are provided, as well as illustrations of important morphological characters of Xizicus (Paraxizicus) biprocerus (Shi & Zhang,1996) and Xizicus (Paraxizicus) anisocercus Liu, 2004 are given.